Molecular mechanism of PilZ adaptor protein mediated cyclic di-GMP signaling - Xin, Lingyi (2018)
The universal bacterial second messenger molecule cyclic di-GMP interacts with a wide variety of receptors to regulate cellular processes. Free-standing PilZ domain proteins are the most prevalent cyclic di-GMP effectors, and elucidating their functions is essential for understanding the role of cyclic di-GMP in many bacteria. In this study, we found that the single-domain PilZ protein PA4608 (named as MapZ-methyltransferase associated PilZ) from the opportunistic pathogen Pseudomonas aeruginosa directly interacts with a chemotaxis methyltransferase CheR1 in the presence of cyclic di-GMP. We demonstrated that cyclic di-GMP inhibits the methylation of chemoreceptor by CheR1 through MapZ. We found that cyclic di-GMP and the pole-localized MapZ control the frequency of swimming direction reversal and persistence of runs through flagellar motor to mediate swimming motility and surface attachment during biofilm formation. Furthermore, we found that elevated cellular cyclic di-GMP levels suppress flagellar motor switching through MapZ to cause decreases in swimming reversal frequency, which is controlled by a pool of cyclic di-GMP governed by a specific set of cyclic di-GMP phosphodiesterases (PDEs), with the three PDEs DipA, RbdA and NbdA exerting the greatest control on flagellar motor switching. To understand the molecular mechanism in cyclic di-GMP mediated protein regulation, we solved the co-crystal structure of the PilZ adaptor protein MapZ in complex with cyclic di-GMP and its protein target CheR1. The co-crystal structure, together with the structure of free CheR1, revealed that the binding of cyclic di-GMP induces dramatic structural changes in MapZ that are crucial for CheR1 binding. Importantly, restructuring and repositioning of two C-terminal helices enable MapZ to disrupt the active site of CheR1 by dislodging a structural domain. The crystallographic observations are reinforced by protein-protein binding and single cell-based flagellar motor switching analysis. Our studies further suggest that the regulation of chemotaxis by cyclic di-GMP through MapZ orthologs/homologs is widespread in proteobacteria, and that the use of allosterically regulated C-terminal motifs could be a common mechanism for PilZ adaptor proteins. Collectively, the studies unveil a novel cyclic diGMP regulatory mechanism to control flagellar motor switching through the PilZ adaptor protein and advance our understanding of the molecular mechanism of cyclic di-GMP signaling.